2012
DOI: 10.1002/alr.21126
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis and literature review of techniques to achieve hemostasis in endoscopic sinus surgery

Abstract: Meta-analysis of 1148 patients concludes that hemostasis during FESS is best conducted using TIVA, preoperative steroids, and topical local anesthetic at a 1:200,000 concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
1
6

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 15 publications
4
60
1
6
Order By: Relevance
“…27 Se a definição de TIVA é ou não apropriada para eles, a importân-cia da hipotensão induzida por alguns agentes intravenosos é óbvia. 20,21,28 Propofol e remifentanil são apenas alguns deles.…”
Section: Discussionunclassified
“…27 Se a definição de TIVA é ou não apropriada para eles, a importân-cia da hipotensão induzida por alguns agentes intravenosos é óbvia. 20,21,28 Propofol e remifentanil são apenas alguns deles.…”
Section: Discussionunclassified
“…Although the vasoconstrictive effect of oxymetazoline is not as powerful as some of these other agents, it has become one of the most commonly used given its favorable safety profile. [4][5][6] Cocaine has been associated with tachycardia, hypertension, and enhancement of the excitatory effects of epinephrine. 7,8 These side effects, coupled with its addictive potential, have led to a decline in the use of cocaine over the past 30 years.…”
mentioning
confidence: 99%
“…A meta-analysis performed by Khosla et al [26] reviewed comparison of intraoperative blood loss between preoperative steroid-administered and placebo groups. Two studies included in this evaluation concluded that preoperative steroids improved surgical blood loss [22,27].…”
Section: Discussionmentioning
confidence: 99%